PENGARUH PEMBERIAN POSISI SEMI FOWLER TERHADAP KESTABILAN POLA NAPAS PADA PASIEN TB PARU DI IRINA C5 RSUP PROF Dr. R. D. KANDOU MANADO - Majampoh, Aneci Boki; Rondonuwu, Rolly; Onibala, Franly (JURNAL KEPERAWATAN, 2015)
Abstract: Provision of Semi-fowler’s position at pulmonary tuberculosis patients have been conducted as one way to help reduce shortness of breathing. The right position for patients with cardiopulmonary disease is given Semi-Fowler’s position with degree of slope 30-45°. Purpose to know effect of Semi-Fowler’s position on the stability of breathing pattern in patients with pulmonary tuberculosis. Method quantitative research with pre-experimental research type, one group pre-post test design by using total sampling technique. Sample of 40 respondents. Data collected using observation sheet and SOP Semi-Fowler’s position. Data were processed using computer program Wilcoxon Signed Ranks Test at 95% significance level (α 0,05). Result respiratory frequency before being given a Semi-Fowler’s position, including the frequency of moderate to severe shortness of breathing and respiratory frequency after being given the Semi-Fowler’s position including normal breathing frequency. Conclusion effect of Semi-Fowler’s position against the stability of breathing pattern on pulmonary tuberculosis patient with p value = 0,000. Recommendation Releasing evidence based practice, especially in the management of pulmonary tuberculosis patient that experience shortness of breath to improve quality of breathing with nonpharmacological therapy. Keyword: Semi-Fowler’s, Stability Breathing Pattern. Abstrak: Pemberian posisi semi fowler pada pasien TB paru telah dilakukan sebagai salah satu cara untuk membantu mengurangi sesak napas. Posisi yang tepat bagi pasien dengan penyakit kardiopulmonari adalah diberikan posisi semi fowler dengan derajat kemiringan 30 - 45°. Tujuan untuk diketahui pengaruh pemberian posisi semi fowler terhadap kestabilan pola napas pada pasien TB paru. Metode kuantitatif dengan jenis penelitian praeksperimental desain satu kelompok pre-post test, tekhnik total sampling. Sampel 40 responden. Pengumpulan data dengan menggunakan lembar observasi dan SOP pemberian posisi semi fowler. Data diolah dengan program komputer uji Wilcoxon Signed Ranks Test tingkat kemaknaan 95% (α 0,05). Hasil penelitian frekuensi pernapasan sebelum diberikan posisi semi fowler termasuk frekuensi sesak napas sedang sampai berat dan frekuensi pernapasan setelah diberikan posisi semi fowler termasuk frekuensi pernapasan normal. Simpulan Terdapat pengaruh pemberian posisi semi fowler terhadap kestabilan pola napas pada pasien TB paru dengan nilai p value = 0,000. Rekomendasi Mewujudkan evidence based practice terutama dalam hal pengelolaan pasien TB paru yang mengalami sesak napas untuk meningkatkan kualitas pernapasannya dengan terapi nonfarmakologi. Kata kunci: Semi Fowler, Kestabilan Pola Napas.